Epidemiological characteristics of influenza-like illness during 2021 - 2022 in Xiamen city: a hospital-based sentinel surveillance data analysis - Min REN; Beile REN; Junneng ZHANG (Editorial Office of Chinese Journal of Public Health, 2023)
ObjectiveTo describe epidemiological characteristics of influenza-like illness (ILI) cases reported during 2021 - 22 by sentinel hospitals in Xiamen city, Fujian province for providing evidence to influenza prevention and control. Methods Demographic and medical information for 6 018 ILI cases reported by sentinel hospitals in Xiamen city from August 2021 to July 2022 were collected from National Influenza Surveillance Information System. Epidemiological and pathogenetic characteristics of the ILL cases were analyzed statistically. ResultsOf all the registered ILI cases, 51.99% (3 129) were male and 48.01% (2 889) were female; 49.72% (2 992) were at ages of 3 - 6 years; and 52.64% (3168) were reported during June 2022. For 2 794 pharyngeal swab specimens randomly collected from 46.43% of all cases, 1 683 were positive for influenza virus nucleic acid, with a detection rate of 60.24%. Single-strain infection were detected among most (1 536, 91.27% ) of the cases positive for influenza virus and the ratios of the isolated strains for the single infections were 57.75% for influenza A H3N2, 31.91% for influenza B Victoria lineage, and 1.60% for influenza A H1N1, respectively. The most detected co-infections were caused by influenza B Victoria lineage combined with human metapneumovirus infection, which was identified in 32 cases, accounting for 1.90% of the nucleic acid-positive ILI cases. ConclusionAccording to hospital-based sentinel surveillance, the ILI incidence showed a mono-peak in summer season and mainly caused by influenza A H3N2 and 3 - 6 years children were more susceptible to the influenza-like infection during 2021 - 22 in Xiamen city.